Kedudukan Hukum dan Hak Waris Anak Hasil Donor Sperma Menurut Hukum Islam, KUH Perdata dan Hukum Adat - Mhd Fakhran Hadyan Simbolon; Tan Kamello; Utary Maharany (Jurnal Hukum Lex Generalis, 2025)
The development of assisted reproductive technology has raised various new legal issues, one of which is the legal status and inheritance rights of children born from sperm donation. This research analyzes the legal status of children born from sperm donation according to three legal systems applicable in Indonesia: Islamic Law, Civil Code, and Customary Law. The research findings show that these three legal systems provide different treatment for children born from sperm donation, both in terms of legal status and inheritance rights. Islamic Law views children born from sperm donation as illegitimate children who only have lineage relationship with their mothers, Civil Code provides flexibility with several possible statuses, while Customary Law emphasizes juridical reality rather than biological reality in determining children's legal status.